Acupoint Stimulation for Enhanced Recovery After Colon Surgery: A Prospective Multicenter Randomized Controlled Trial - Lu Z; Luo A; Min S; Dong H; Xiong Q; Li X; Deng Q; Liu T; Yang X; Li C; Zhao Q; Xiong L (Journal of Multidisciplinary Healthcare, 2022)
Zhihong Lu,1,* Ailin Luo,2,* Su Min,3,* Hailong Dong,1 Qiuju Xiong,3 Xinhua Li,2 Qingzhu Deng,2 Tingting Liu,1 Xue Yang,1 Chen Li,4 Qingchuan Zhao,5 Lize Xiong1,6 1Department of Anaesthesiology and Perioperative Medicine, Xijing Hospital, Fourth Military Medical University, Xi’an, People’s Republic of China; 2Department of Anaesthesiology, Tongji Hospital, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Anaesthesiology, First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Medical Statistics, Fourth Military Medical University, Xi’an, People’s Republic of China; 5Xijing Hospital of Digestive Diseases, Fourth Military Medical University, Xi’an, People’s Republic of China; 6Translational Research Institute of Brain and Brain-Like Intelligence and Department of Anesthesiology, Shanghai Fourth People’s Hospital Affiliated to Tongji University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhihong Lu; Lize Xiong, Department of Anesthesiology and Perioperative Medicine, Xijing Hospital, Fourth Military Medical University, Changle West Road127, Xi’an, Shaanxi, 710032, People’s Republic of China, Tel +86-29-84775337 ; Tel +86-29-84772126, Email deerlu23@163.com; xlzmzk@163.comPurpose: The aim of this study was to evaluate the efficacy of transcutaneous electrical acupoint stimulation (TEAS) in improving bowel function and thus shortening hospital stay after laparoscopic colon surgery within the ERAS pathway.Patients and Methods: From November 2016 to March 2018, 100 patients who underwent elective colon surgery were enrolled and 94 finished study (n = 47 for each) in three university hospitals. Patients in the TEAS group received TEAS 30 min before surgery and once a day for 3 days after surgery, while those in the Control Group received no stimulation. Primary outcome was the time to discharge.Results: Compared with standardized postoperative care, TEAS resulted in a shorter time to first flatus (P=0.03) and time to first defecation (P=0.03), as well as a reduction in the length of hospital stay (P=0.02). Median patient-controlled analgesia (PCA) deliveries and PCA attempts at 24h, 48h and 72h after surgery were less in the TEAS group (P< 0.01). No evidence of significant advantages in postoperative pain intensity, nausea, vomiting, sleeping quality and expenses was found in the TEAS group.Conclusion: Perioperative TEAS further shortens the time to meet discharge criteria after laparoscopic colon surgery in patients under ERAS strategy.Keywords: transcutaneous electrical acupoint stimulation, colon surgery, laparoscopy, ERAS